The Constitutionality of the Presidential Threshold Provisions in Indonesian Election Law: A Juridical Review of Law No. 7/2017 on General Elections - Putra, Irman; Lubis, Arief Fahmi (Westscience Press, 2024)
This study critically examines the constitutionality of the presidential nomination threshold provision stipulated in Law No. 7/2017 on General Elections. By conducting a juridical analysis, this research explores the legal and constitutional underpinnings of the presidential nomination threshold, which mandates a minimum percentage of parliamentary seats or popular votes for a political party or coalition to nominate a presidential candidate. The analysis explores the historical context, legislative intent and judicial interpretation of the threshold provision. It also assesses the impact of these provisions on political competition, electoral fairness and democratic representation in Indonesia. It identifies potential constitutional conflicts and proposes legal reforms to enhance the legitimacy and inclusiveness of the presidential election process. Through a comprehensive legal review, this research aims to contribute to the ongoing discourse on electoral law and democratic governance in Indonesia.